Effect of Diatom Silica Content on Copepod Grazing, Growth and Reproduction - Liu, Hongbin; Chen, Mianrun; Zhu, Feng; Harrison, Paul J. (Frontiers in Marine Science, 2016)
Diatoms are often a major food source for zooplankton and contribute significantly to vertical POC flux through sinking of dead cells, aggregates and zooplankton fecal pellets. The silica content of diatoms varies among different species and within a species growing under different environmental conditions and physiological status. However, to-date there has been no investigation of the effect of diatom silica content on zooplankton grazing, growth and reproduction. We conducted a series of experiments using the diatom Thalassiosira weissflogii with different silica content achieved by growth under high and low light and these cells were fed to a copepod, Parvocalanus crassirostris. Our results show that this copepod strongly preferred cells with low silica content over high silica-containing cells, with the ingestion rate on low silica diatoms being 2-3 times higher than that on high silica diatoms. Fecal pellet production rate was significantly higher for copepods feeding on highly silicified cells. Furthermore, copepod growth rate (measured as an increase in wet weight), egg production rate and hatching success were all severely compromised under a high silica diatom diet. Females of P. crassirostris feeding on a low silica diatom diet produced an average 90 eggs during a one day incubation, while those fed with high silica diatoms produced only 11 eggs per day. Similarly, the hatching success during a 3-day period was 82 ± 17% and 23 ± 36% for the low and high silica diatom treatments, respectively, with zero success observed in 65% of the females feeding on high Si diatoms. Our findings have important ecological implications for the biological pump and may alter our previous view of the role of diatoms in planktonic food webs and the role of the degree of silicification in controlling amount of POC flux to deeper waters.